Framing Media terhadap Isu Palestina: Analisis Wacana Pemberitaan di Media Barat dan Media Timur Tengah : - Qostholani, Afiv Mujadi; Rukayah, Siti; Nuraini, Vita; Salisah, Nikmah Hadiati (Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze how Western and Middle Eastern media frame the Palestinian issue in their reporting. The research method uses a critical discourse analysis approach. This study explores the differences in narrative, perspective, and language strategies used by both media groups in conveying the Palestinian conflict. Data was taken from a number of news articles published by Western media, namely CNN, BBC, and The New York Times. Middle Eastern media included Al Jazeera, Al Arabiya, and Press TV. The results of the study show that Western media tend to use a frame that emphasizes Israeli security issues, pseudo-neutrality, and the labeling of resistance groups as terrorists, while Middle Eastern media focus more on humanitarian aspects, occupation, and the Palestinian people’s struggle. These findings reveal how ideology and political interests shape the way the media represent reality and their impact on global public perception of the Palestinian conflict